The Implementation Of The Principle Of Freedom Of Contract In Providing Legal Protection For Workers Under Indefinite-Term Employment Contract At CV Soloarsi Studio - Tia Nur, Fadhliyah; Suryono , Arief (CV. Inara, 2024)
The establishment of worker protection arises from the contractual agreement between employers and employees. The legal relationship between these parties is constituted through an employment contract. The principle of freedom of contract, as stipulated within Article 1338 paragraph (1) of the Civil Code, is embodied in employment contract. Employment contracts that adhere to this principle can prevent the commodification of workers. However, within its practical endeavor, the principle of freedom of contract is frequently compromised in employment contract, leading to an imbalance of rights and obligations between workers and employers. CV Soloarsi Studio, a limited liability company, distinguishes between two types of employment agreements: fixed-term employment contract (PKWT) and indefinite-term employment contract (PKWTT). The aim of this research is to investigate and comprehend the application of the principle of freedom of contract in providing legal protection for workers under indefinite-term employment contract (PKWTT) at CV Soloarsi Studio. The research employed normative methodology, involving the examination of library materials and secondary data. The findings of this research indicate that legal protection for workers can be categorized into three types: economic, social, and technical protection. CV Soloarsi Studio, through its indefinite-term employment contract (PKWTT), has provided legal protection across these three categories. This compliance is evidenced by the allocation of rights and obligations to workers in alignment with the provisions stipulated by Law of Republic of Indonesia Number (No.) 6 of 2023, which ratifies Government Regulation of the Republic of Indonesia in Lieu of Law of Republic of Indonesia Number (No.) 2 of 2022 concerning Job Creation into Law of Republic of Indonesia (UU 6/2023).